Dutch Sectoral Energy Intensity Developments in International Perspective, 1987-2005 - Peter Mulder; Henri L.F. de Groot (Tinbergen Institute, 2012)
This paper makes use of a new dataset to investigate energy intensity developments in the Netherlands over the period 1987-2005. The dataset allows for a comparison with 18 other OECD countries. A key feature of our analysis is that we combine a cross-country perspective with a high level of sectoral detail, covering 49 sectors. Particularly innovative is our evaluation of energy intensity developments in a wide range of Service sectors. We find that across sectors energy intensity levels in the Netherlands on average decreased only marginally, and increased in Services. This performance is in general worse than the OECD average, especially between 1987 and 1995. Changes in the sectoral composition of the economy play an important role in explaining aggregate trends. In the Manufacturing sector about half of the efficiency improvements were undone by a shift towards a more energy-intensive industry structure, while in the Service sector about one-third of the decrease in efficiency was undone by a shift towards a less energy-intensive sector structure.
urn:NBN:nl:ui:31-1871/38463
Keywords: O13; O47; O5; Q43; 330; Energy Intensity; Decomposition; Sectoral Analysis; Energiekonsum; Branche; Niederlande; Vergleich; OECD-Staaten